Trends of overweight and obesity prevalence in school-aged children among Henan Province from 2000 to 2019 - Zhang, Yuhao; Lou, Hao; Huang, Ye; Wang, Ruijuan; Wen, Xiao; Wu, Cuiping; Hao, Changfu; Li, Ran; Gao, Genli; Lou, Xiaomin; Wang, Xian (Frontiers in Public Health, 2022)
Objectives Overweight and obesity are harmful to human health. However, the latest trends of Chinese childhood overweight and obesity prevalence are not available. The aim of this study was to examine the trends from 2000 to 2019 among students in China. Methods We analyzed data of 66 072 students in the Chinese National Survey on Students’ Constitution and Health from 2000 to 2019. Overweight and obesity were defined based on the standard formulated by the International Obesity Task Force (IOTF standard), the World Health Organization (WHO standard), and the Working Group on Obesity in China (WGOC standard), respectively. The χ2 test was used to test the trends of overweight and obesity prevalence and logistic regression was conducted to evaluate the prevalence odds ratios of boys vs. girls and urban vs. rural areas. Results The prevalence of obesity/overweight and obesity combined was 6.03%/23.58% (IOTF standard), 10.56%/25.88% (WGOC standard) and 10.75%/29.69% (WHO standard) in 2019. From 2000 to 2019, according to the WGOC standard, the prevalence increased from 2.51% to 10.56% for obesity and increased from 9.81% to 25.88% for overweight and obesity combined (P for trend < 0.001). Obesity/overweight and obesity were greater problems in boys than girls and urban than rural areas, but urban-rural differences decreased over time. Conclusion Overweight and obesity prevalence increased significantly in children and adolescents in China from 2000 to 2019. The prevalence of overweight and obesity in rural areas may contribute to a large percentage of children with overweight and obesity.